MEANING OF SIGN FOUND IN IPHONE 13 ADVERTISEMENT VIDEO - Niscita, Ida Bagus Brian; Sosiowati, I Gst. Ayu Gde; Soethama, Putu Lirishanti (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTThis study entitled Meaning of Sign Found in iPhone 13 Advertisement Video. This study focusses on theanalysis of verbal and visual sign in the video. Its aims are to identifying the kinds of verbal and visual signand analysing the meaning of verbal and visual sign of implied in the video. Documentation method is usedto collected the data and the data was qualitatively analyzed. Dyer’s (1982), Barthes (1964), and Chapman’s(2010) theory were used in this study.Keywords: advertisement; verbal signs; visual signs.ABSTRAKPenelitian ini berjudul Makna Tanda yang Ditemukan pada Video Iklan iPhone 13. Penelitian ini berfokuspada analisis tanda verbal dan visual dalam video. Tujuannya adalah untuk mengidentifikasi jenis tandaverbal dan visual dan menganalisis makna dari tanda verbal dan visual yang tersirat dalam video. Metodedokumentasi digunakan untuk mengumpulkan data dan data dianalisis secara kualitatif. Teori Dyer (1982),Barthes (1964), dan Chapman (2010) digunakan dalam penelitian ini.Kata kuci: iklan; tanda iklan; tanda visual.